Barriers and facilitators to participation in workplace health promotion (WHP) activities: results from a cross‐sectional survey of public‐sector employees in Tasmania, Australia. (19th January 2017) - Kilpatrick, Michelle; Blizzard, Leigh; Sanderson, Kristy; Teale, Brook; Jose, Kim; Venn, Alison
Abstract : Issue addressed: Workplaces are promising settings for health promotion, yet employee participation in workplace health promotion (WHP) activities is often low or variable. This study explored facilitating factors and barriers associated with participation in WHP activities that formed part of a comprehensive WHP initiative run within the Tasmanian State Service (TSS) between 2009 and 2013. Methods: TSS employee ( n = 3228) completed surveys in 2013. Data included sociodemographic characteristics, employee‐perceived availability of WHP activities, employee‐reported participation in WHP activities, and facilitators and barriers to participation. Ordinal log‐link regression was used in cross‐sectional analyses. Results: Significant associations were found for all facilitating factors and participation. Respondents who felt their organisation placed a high priority on WHP, who believed that management supported participation or that the activities could improve their health were more likely to participate. Time‐ and health‐related barriers were associated with participation in fewer activities. All associations were independent of age, sex, work schedule and employee‐perceived availability of programs. Part‐time and shift‐work patterns, and location of activities were additionally identified barriers. Conclusion: Facilitating factors relating to implementation, peer and environmental support, were associated with participation in more types of activities, time‐ and health‐related barriers were associated with less participation. So what?: Large and diverse organisations should ensure WHP efforts have manager support and adopt flexible approaches to maximise employee engagement. Abstract : It is important to better understand how organisations can maximise employee engagement in workplace health promotion (WHP). This study identified WHP implementation strategies that were associated with participation in more types of WHP activities, and the barriers associated with less participation. The findings provide evidence from the 'real‐world' delivery of WHP by a large public‐sector organisation across many different work settings.